Perencanaan Partisipatif dalam Pembangunan Hutan Rakyat di Kabupaten Jombang - Widiawan, Dwi Harjo (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2017)
This paper examines participatory planning in forestry development in private forests. Results: Findings showed that participatory planning in forestry development in private forests in Jombang at this stage of deliberations level RT, meeting farmers' groups and programming villages have been carried out in accordance with the planning stages, while the next process is still hampered commitment issues and policies as well as the involvement of farmer. Actors involved include farmers, forestry extension, forestry businesses and community leaders. In conclusion, participatory planning in forestry development in private forests in Jombang carried out with the stage of investigation, the formulation of the problem, identification of carrying capacity, formulation of objectives, set out the steps, and budgeting. Forestry extension is an actor who has a bigger role in the participatory planning in forestry development.